Exanthematic lesion manifested after acute alcohol intoxication: case report (Research, Society and Development, 2021)
Introduction: Of the many alcohol-related disorders present in individuals referred to emergency care departments, acute alcohol intoxication is the most frequent, being a clinically harmful condition that usually occurs after drinking a large amount of alcohol. Objective: to explain a case of a patient who, after acute alcohol intoxication, had exanthematic lesions, especially on the face, characteristic of rosacea. Methodology: This article is a clinical case study with a qualitative and descriptive perspective, which consists of a research that, in general, takes place with direct data collection, in which the researcher is the indispensable instrument. Case description: This is a 24-year-old male patient who, after excessive alcohol intake, with symptoms of malaise, asthenia, drowsiness, decreased visual acuity, tachycardia, nausea, headache, pupillary dilation, slurred speech, hypoglycemia and loss of control of body movements, in which the therapy consisted of intravenous hydration, infusion of glucose serum and replacement of thiamines. In addition to these symptoms, the patient presented, in line with the pruritus, morbilliform maculopapular exanthematic lesions on the face, as shown in Image 1, characteristic of rosacea. Conclusion: Acute alcohol intoxication is a clinically harmful condition that usually occurs after drinking a large amount of alcohol. It can manifest itself clinically in several ways and have behavioral, cardiac, gastrointestinal, pulmonary, neurological and metabolic effects, as well as dermatological, as exposed in the present study.